Multiplex ligation-dependent probe amplification copy number variant analysis in patients with acquired long QT syndrome - Williams, Victoria S.; Cresswell, Carl J.; Ruspi, Gerhard; Yang, Tao; Atak, Thomas C.; McLoughlin, Matthew; Ingram, Christiana D.; Ramirez, Andrea H.; Roden, Dan; Armstrong, Martin (Europace (London, England), 2015)
Thirteen genetic loci map to families with congenital long QT syndrome (cLQT) and multiple single nucleotide mutations have been functionally implicated in cLQT. Studies have investigated copy number variations (CNVs) in the cLQT genes to ascertain their involvement in cLQT. In these studies 3-12% of cLQT patients who were mutation negative by all other methods carried CNVs in cLQT genes. Prolongation of the QT interval can also be acquired after exposure to certain drugs [acquired LQT (aLQT)]. Single nucleotide mutations in cLQT genes have also been associated with and functionally implicated in aLQT, but to date no studies have explored CNVs as an additional susceptibility factor in aLQT. The aim of this study was to explore the contribution of CNVs in determining susceptibility to aLQT. In this study we screened the commonest cLQT genes (KCNQ1; KCNH2; SCN5A; KCNE1, and KCNE2) in a general population of healthy volunteers and in a cohort of subjects presenting with aLQT for CNVs using the multiplex ligation-dependent probe amplification method. Copy number variants were detected and confirmed in 1 of 197 of the healthy volunteers and in 1 of 90 subjects with aLQT. The CNV in the aLQT subject was functionally characterized and demonstrated impaired channel function. Copy number variation is a possible additional risk factor for aLQT and should be considered for incorporation into pharmacogenetic screening of LQTS genes in addition to mutation detection to improve the safety of medication administration.